2021
DOI: 10.1016/j.maturitas.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender gap in spinal cord injury research: Focus on cardiometabolic diseases. A mini review

Abstract: Cardiometabolic disease (CMD) is among the leading causes of morbidity and mortality in people with a spinal cord injury (SCI). Despite well-acknowledged sex and gender differences in CMD in the general population, they remain insufficiently studied in persons with SCI. To describe the landscape of sex and gender in SCI research, we searched the literature for systematic reviews on cardiometabolic health in this population. Out of 15 systematic reviews identified, only 9 provided meaningful information on sex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…Such factors include age, sex, injury characteristics and injury duration, major lifestyle indices (e.g., diet, smoking and alcohol intake), prophylactic and therapeutic medication use, and parameters of body morphology. Second, while SCI is predominantly a men's condition with around 85% of this population being male, many researchers purposively exclude women from research in order to ensure more homogeneity in study sample [ 70 ]. We discuss this issue in depth elsewhere [ 70 ], however, a general suggestion to overcome this and other common problems in SCI research (e.g., difficulties to disaggregate results per injury characteristics or injury duration due to small sample size) would be to focus on collaborative research either through international consortia or multi-centric studies or to engage advanced statistical approaches in order to generate reliable evidence [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such factors include age, sex, injury characteristics and injury duration, major lifestyle indices (e.g., diet, smoking and alcohol intake), prophylactic and therapeutic medication use, and parameters of body morphology. Second, while SCI is predominantly a men's condition with around 85% of this population being male, many researchers purposively exclude women from research in order to ensure more homogeneity in study sample [ 70 ]. We discuss this issue in depth elsewhere [ 70 ], however, a general suggestion to overcome this and other common problems in SCI research (e.g., difficulties to disaggregate results per injury characteristics or injury duration due to small sample size) would be to focus on collaborative research either through international consortia or multi-centric studies or to engage advanced statistical approaches in order to generate reliable evidence [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, while SCI is predominantly a men's condition with around 85% of this population being male, many researchers purposively exclude women from research in order to ensure more homogeneity in study sample [ 70 ]. We discuss this issue in depth elsewhere [ 70 ], however, a general suggestion to overcome this and other common problems in SCI research (e.g., difficulties to disaggregate results per injury characteristics or injury duration due to small sample size) would be to focus on collaborative research either through international consortia or multi-centric studies or to engage advanced statistical approaches in order to generate reliable evidence [ 70 ]. Third, the loss of metabolically active skeletal muscle and limitations in mobility result in decreased basal metabolic rate and resting energy expenditure already within weeks since injury [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current literature is predominantly based on males, albeit sex is a significant determinant of adiposity in the general population [100]. There are established hormonal changes across different reproductive stages that influence adiposity in females, and, as such, this field has yet to be explored [101].…”
Section: Knowledge Gaps and Future Researchmentioning
confidence: 99%
“…As for the duration of injury, factor analysis has been challenging as age is highly correlated with injury duration (36,37). A longitudinal study has shown that quality of life, activity, and participation declines with the duration of injury, along with age and age of onset (38).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, females were grossly underrepresented in our analysis (526/3878 or 13.5%), thus, our analysis could only be generalized to males. Despite sex is a critical determinant of cardiovascular risk, the SCI researches rarely included females or performed female-specific analyses and we discussed this phenomenon elsewhere [ 38 ].…”
Section: Discussionmentioning
confidence: 99%